Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

how do you solve y=2x+7; 3x-y=-9 using substitution method. Explain please!!

Sagot :

The y's value is given in the first equation. [tex]y=2x+7[/tex] . Now to solve, we will, plug it's value in the second equation.

[tex]3x-(2x+7)=-9\\ \\ 3x-2x-7=-9\\ \\ x=-9+7\\ x=-2\\ [/tex]

Now we have x's value, we will plug it's value in the first equation.(We can plug it in the second one too, but plugging it the first one will make it easier.)

[tex]x=-2\\ y=2x+7\\ y=2\cdot -2+7\\ y=-4+7\\ y=3[/tex]




{ y = 2x + 7
{ 3x - y = - 9

Substitute y for 2x + 7 in the 2nd equation:

3x - y = - 9
3x - ( 2x + 7 ) = - 9
3x - 2x - 7 = - 9
3x - 2x = - 9 + 7
x = - 2

Substitute - 2 for x in one of the equations:

y = 2x + 7
y = 2.( - 2 ) + 7
y = - 4 + 7
y = 3

S = { - 2 , 3 }
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.